Numerical studies on the separation performance of liquid-liquid hydrocyclone for higher water-cut wells - Osei, H. (Institute of Physics Publishing, 2015)
Liquid-liquid hydrocyclones have nowadays become very useful in the oil industry because of their numerous applications. They can be installed downhole in the case of a well that produces higher water-oil ratios. The design of a liquid-liquid hydrocyclone for such a task is critical and every geometric part of the hydrocyclone has a part to play as far as separation is concerned. This work, through validated numerical technique, investigated the liquid-liquid hydrocyclone performance for the cases of single-inlet and dual-inlets, with different upper cylindrical lengths, specifically, 30mm and 60mm.It was observed that the hydrocyclones with the 30mm upper cylindrical section perform better than the ones with 60 mm upper cylindrical section. It was again noted that, even though higher number of tangential inlets increases the swirl intensity, they have the tendency to break up the oil droplets within the hydrocyclone because of increasing shear and jet flow interaction.